DISCLOSURE DARI PERSPEKTIF PERUSAHAAN DAN PENGGUNA, MUNGKINKAH MENCAPAI EKUILIBRIUM ? - Evita Puspitasari (Program Studi Manajemen, 2018)
There are so much information available in security markets provided by many sources. These information then are used by many users for decision making. Disclosure is one of thoose containing more complete and more detail information a specific company. Inpresenting disclosure, company is facing trading off: how to present appropriate disclosure without eliminating users’ rights and preventing competitors in gainig private information. By collecting and analyzing disclosure from articles and researches, most from Accounting Review and Journal of Accounting. I found company will consider both costs and benefits in deciding which disclosure will be presented. Distrubing effect, the use of private information by potential competitors, is one of the company considerations. I concluded, since there always be the third party, equilibrilium disclosure will never be reached.